Comparative analysis of foot arch type on explosive power and stability of Kabaddi athlete - Utama, Made Bang Redy; Subekti, Maryoto; Ihsani, Sri Indah; S, Adi; Fastabikulkhoirot, Fastabikulkhoirot (Jurnal Ilmu Keolahragaan, 2025)
Background. Kabaddi is a sport that requires good physical abilities, especially in kabaddi, where the legs are very important for both defensive and offensive players. Variations in the type of foot arch can affect weight distribution, movement efficiency, and postural stability. Objectives. This study aims to analyze the influence of foot arch type (normal arch vs. high arch) on leg muscle explosive power and balance among Kabaddi athletes from Bali"™s provincial training camp. Methods. The research employs a quantitative comparative approach with a cross-sectional design. The sample consists of 25 athletes (12 males and 13 females) selected through purposive sampling. Data were collected using the Staheli Footprint Index (SFI) to assess foot shape, a vertical jump test for explosive power, and a stork stand test for balance. Statistical analysis was conducted using the Shapiro-Wilk test for normality and the Mann-Whitney U test for group comparison. Results. Based on the statistical analysis using the Mann-Whitney U test, this study concludes that there are no significant differences between normal arch and high arch foot types in terms of leg muscle explosive power (p = 0.969) and balance (p = 0.238) among Kabaddi athletes from Bali"™s provincial training camp. Conclusion. Further studies with larger and more comprehensive samples are recommended for more accurate results. These findings suggest that foot arch shape is not a primary determinant of Kabaddi athlete performance, and that other factors such as specific training and muscle strength may have a greater impact.